PENYEBAB DAN KONDISI PSIKOLOGIS NARAPIDANA KASUS NARKOBA PADA REMAJA - Afrinisna, Rizki Yuvita (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstractThis study aims to determine the cause of youth abusing drugs, understanding adolescent psychological condition while in prison and knowing adolescent life plans after getting out of prison. The research method used was a qualitative study with phenomenological approach. The method of data collection using interviews and observations which using two subjects. Based on the results of the study showed that teens abusing drugs cause the lack of communication within the family so that makes teenagers perform conformity to join a group. Increased emotional causes less mature adolescents not yet skilled enough to face the problems and make responsible decisions while in her social environment close to the drug. As a result, without thinking, and to meet the demands of social, youth who are in the group ended up following the advice given by the group to abusing drugs as a way out to resolve the problem. The psychological conditions experienced by inmates teenage drug case was lost concentration and daydreaming, deep sadness, a crisis of confidence, excessive suspicion, resentment, depression and anxiety and become avoidance of other person, introvert and antisocial. Plan for life convicts adolescent drug case after the detention period is to stay away from drugs after and acceptable and played back in the community and get a decent job. Keywords: psychological conditions, juvenile inmate drug case